Effectiveness of theory based intervention using social media to reduce urinary incontinence among postpartum women in Hebron city hospitals: randomized controlled trial - Mesk, Zeenat; Abdul Manaf, Rosliza; Kadir Shahar, Hayati; Mohd Nazan, Ahmad Iqmer Nashriq; Amro, Akram (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Urinary incontinence (UI) is a condition which is common and is closely linked to vaginal delivery. Pelvic floor muscle exercise (PFME) are considered the first line management of UI and regular practice of PFME is a key factor in its effectiveness. This study was designed to investigate the effectiveness of theory-based intervention using social media to reduce UI among postpartum women. Methods: This is a randomized controlled trial with the final number of recruited participants of 104. The participants were assigned randomly either to control or intervention groups and were followed up at three and six months. The primary outcome of this study was severity of UI. Adherence to exercises was the secondary outcome. Results: After the intervention, at three months and six months follow-up, there were significant differences between the two groups regarding the practice of PFMEs (p≤ 0.05). Friedman’s analysis of variance showed that there was a significant difference in respect of the exercise adherence rating scale among the intervention group at baseline, at three months and post six months (p≤ 0.05). In the intervention group at baseline the mean (standard deviation, sd) of the International Consultation on Incontinence Questionnaire Short Form was 3.00 (1.94) whereas at three months it decreased to 1.96 (1.69), which decreased further to 1.04 (0.51) at six months. Conclusion: theory-based education delivered through social media is a feasible and effective way of increasing the practice of PFMEs, and can lead to decrease of severity UI.